Introducing Daoism - Kohn, Livia (World religions, 2009)
Introduction : background to Daoism -- Pt. I. Foundations -- The Dao that can't be told -- At ease in perfect happiness -- From health to immortality -- Cosmos, gods, and governance -- Pt. II. Development -- Major schools of the Middle Ages -- Ethics and community -- Creation and the pantheon -- Resligious practices -- Pt. III. Modernity -- Modern Daoism -- Reaching for the Dao -- Daoism in China today -- Western adaptations -- Pt. IV. Reflections -- The nature and study of Daoism